Tinjauan Yuridis Terhadap Putusan Onslag Van Rechtvervolging Terhadap Perkara Penipuan dan Penggelapan : (Studi Kasus Pengadilan Tinggi Sulawesi Tenggara Nomor: 168/PID/2021/PT KDI) - Ramlin Ramlin; Kamaruddin Kamaruddin; Faisal Abdaud (Jurnal Hukum Lex Generalis, 2025)
This study examines the decision of the Kendari High Court No. 168/PID/2021/PT KDI, which issued an onslag van rechtvervolging decision regarding allegations of fraud and embezzlement. This research employs doctrinal law research methods, incorporating legislative and conceptual approaches. The study's results indicate that the defendant, M. Ikhtiar's, actions are more appropriately categorised as defaults in business agreements, where the court affirms that not all uncertainties in transactions reflect malicious intent. This decision provides legal protection for the defendant, while the victim, Ilham Iskandar, faces challenges in recovering losses. The implications of this ruling underscore the importance of distinguishing between criminal and civil disputes, while also encouraging the legal system to be more responsive to the complexities of commercial relationships